2010
DOI: 10.1182/blood.v116.21.3001.3001
|View full text |Cite
|
Sign up to set email alerts
|

A Selective PIM Kinase Inhibitor Is Highly Active In Multiple Myeloma: The Biology of Single Agent and PI3K/AKT/mTOR Combination Activity

Abstract: 3001 PIM kinases co-regulate several important elements of the PI3K/AKT/mTOR pathway in myeloma cells (Munugalavadla V. et al., ASH 2010 submitted abstr.). In this study we show that pan-PIM inhibition suppresses growth in myeloma cell lines, xenografts, and primary patient samples, both as a single-agent as well acting synergistically in combination with PI3K, AKT, and mTOR inhibition. The PIM kinases are a family of 3 ser/thr growth factor- & cytokine-induced proteins hypothesized to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…17 The activity toward PIM kinases is particularly confounding for an analysis in MM, as we have recently shown PIM inhibition to have single-agent activity and a significant synergy in combination with PI3K pathway inhibition. 18,19 Selective inhibition of PI3Kd has recently been shown to have modest growth inhibiting activity in MM. 20 Although the d catalytic isoform does have a non-redundant role in B-cell antigen Receptor (BCR) signaling, 21 it is not clear if this function is important in malignant plasma cells, and evidence for prevalent expression of the d isoform in myeloma cells is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…17 The activity toward PIM kinases is particularly confounding for an analysis in MM, as we have recently shown PIM inhibition to have single-agent activity and a significant synergy in combination with PI3K pathway inhibition. 18,19 Selective inhibition of PI3Kd has recently been shown to have modest growth inhibiting activity in MM. 20 Although the d catalytic isoform does have a non-redundant role in B-cell antigen Receptor (BCR) signaling, 21 it is not clear if this function is important in malignant plasma cells, and evidence for prevalent expression of the d isoform in myeloma cells is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The compound reduced tumor growth of TEL-JAK2/BaF3 subcutaneous tumors in nude mice at 100 mg/kg (TGI = 54%) and 200 mg/kg (TGI = 75%). Scientists at Genentech reported that their pan-Pim inhibitor GNE-652 (structure not disclosed) had picomolar biochemical potency, an excellent selectivity profile, and favorable ADME properties . The molecule showed excellent in vivo efficacy in combination with the PI3K inhibitor 4-(2-(1 H -indazol-4-yl)-6-((4-(methylsulfonyl)piperazin-1-yl)methyl)thieno[3,2- d ]pyrimidin-4-yl)morpholine (GDC-0941).…”
Section: Inhibitors Of the Pim Kinasesmentioning
confidence: 99%
“…Scientists at Genentech reported that their pan-Pim inhibitor GNE-652 (structure not disclosed) had picomolar biochemical potency, an excellent selectivity profile, and favorable ADME properties. 59 The molecule showed excellent in vivo efficacy in combination with the PI3K inhibitor 4-(2-(1H-indazol-4-yl)-6-((4-(methylsulfonyl)piperazin-1-yl)methyl)thieno[3,2-d]pyrimidin-4-yl)morpholine (GDC-0941). Selvita discovered a novel series of Pim kinase inhibitors of which analogue SEL24-B58 (structure not disclosed; IC 50 of 31 nM (Pim-1), 154 nM (Pim-2), 182 nM (Pim-3)) showed in vitro synergy with inhibitors for PI3K, mTOR, JAK1/2, and Bcl-2.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%